2002
DOI: 10.1063/1.1483684
|View full text |Cite
|
Sign up to set email alerts
|

Diameter Effect Curve and Detonation Front Curvature Measurements for ANFO

Abstract: Diameter effect and front curvature measurements are reported for rate stick experiments on commercially available prilled ANFO (ammonium-nitrate/fuel-oil) at ambient temperature. The shots were fired in paper tubes so as to provide minimal confinement. Diameters ranged from 77 mm (» failure diameter) to 205 mm, with the tube length being ten diameters in all cases. Each detonation wave shape was fit with an analytic form, from which the local normal velocity D n , and local total curvature k, were generated a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
29
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 3 publications
2
29
0
Order By: Relevance
“…For this explosive-inert confiner pair, figure 17 shows that the shock polars for the two material almost overlay over a wide region, and this behavior persists for a large range of detonation speeds. Interestingly, experiments by Catanach and Hill [12] and Bdzil et al [13] found very different matches in terms of the measured shock normal angles at the edge of the explosive for this explosive-inert pair and for two different lots of ANFO: Catanach & Hill [12] found edge shock angles of around 50 o (this lot had experienced some separation and had a reduced fuel oil content), while Bdzil et al's [13] results gave edge angles of around 25-29 o . The near overlay of the shock polars seen in figure 17 explains why a unique and consistent interaction between the two materials is not seen, and why the measured shock angle is so sensitive to lot.…”
Section: Discussionmentioning
confidence: 99%
“…For this explosive-inert confiner pair, figure 17 shows that the shock polars for the two material almost overlay over a wide region, and this behavior persists for a large range of detonation speeds. Interestingly, experiments by Catanach and Hill [12] and Bdzil et al [13] found very different matches in terms of the measured shock normal angles at the edge of the explosive for this explosive-inert pair and for two different lots of ANFO: Catanach & Hill [12] found edge shock angles of around 50 o (this lot had experienced some separation and had a reduced fuel oil content), while Bdzil et al's [13] results gave edge angles of around 25-29 o . The near overlay of the shock polars seen in figure 17 explains why a unique and consistent interaction between the two materials is not seen, and why the measured shock angle is so sensitive to lot.…”
Section: Discussionmentioning
confidence: 99%
“…where z is the front height, r is the local radius, and R is the charge radius [1,2]. Equation 1 is fit globally across an entire experimental rate-stick front shape by varying parameters A i and η where 0 < η < 1.…”
Section: Introductionmentioning
confidence: 99%
“…3 In addition, ammonium nitrate prill size and porosity may result in ANFO detonation velocities ranging between 1.5 and 4.0 km/s, owing to different levels of fuel oil absorption within the prills 4,5 or other factors. A broad spectrum of nonideal behavior may be observed in shock front curvature, 6 diameter effects, 7 and interactions with confining material, 8 which cannot be determined without large scale (currently $1 kg or greater) rate stick tests. 6,8 The wide range of non-ideal explosives prohibits large scale characterization of every composition of interest.…”
Section: Introductionmentioning
confidence: 99%
“…A broad spectrum of nonideal behavior may be observed in shock front curvature, 6 diameter effects, 7 and interactions with confining material, 8 which cannot be determined without large scale (currently $1 kg or greater) rate stick tests. 6,8 The wide range of non-ideal explosives prohibits large scale characterization of every composition of interest. Previous attempts to develop small scale characterization tests (e.g., Floret, 9 mushroom, 10 and tiny plate 11 tests) relied on high explosives that can sustain a detonation wave with only a few grams of material.…”
Section: Introductionmentioning
confidence: 99%